Pulmonary Administration: Strengthening the Value of Therapeutic Proximity - Videira, Mafalda A.; Llop, Jordi; Sousa, Carolina; Kreutzer, Bruna; Cossío, Unai; Forbes, Ben; Vieira, Isabel; Gil, Nuno; Silva-Lima, Beatriz (Frontiers in Medicine, 2020)
In recent years inhaled systems have shown momentum as patient-personalized therapies owing these systems regional accumulation. A significant improvement in terms of therapeutic efficacy and/or reduction in side-effects is anticipated from the use of inhaled therapeutic formulations. Nevertheless, whatever safety and efficacy evidence required for inhaled formulations regulatory approval it still poses an additional hurdle to gaining market access. In contrast with the formal intravenously administration the narrower adoption of pulmonary administration even though these formulations therapeutic benefit, might rely on differences in pre-clinical and clinical data provided by the marketing authorization holder to the regulatory authorities. Submitted data from exploratory early clinical/translational research studies differs across authorization holders according to the decision-makers office and depending on the stage of the product/formulation development as this paper discuss. There is evidence of a diverse and inconsistent regulatory framework. Even though an overall trend to support general concepts of good practices exists, concerns over toxicity issues and respiratory safety concerns still subsist. Formal guidance current regulatory environment seeks harmonization and since numerous inhaled formulations are set to be approved in the coming years, a new regulatory framework can emerge from the use of imaging techniques. It is our conviction that if implemented, inhaled nanomedicines might have impact in multiple severe conditions, such as lung cancer, by fulfilling the opportunity for developing tailored treatments while solving dose-related toxicity issues; the most limiting threat in conventional lung cancer clinical management.